Aplicação e transferência de técnicas de qualificação junto à Pastoral da Mobilidade Humana em Corumbá, MS: demandas de fronteira e Migrações Internacionais - Marco Antonio Alves Ribeiro (2022)
RIBEIRO, Marco Antonio Alves. APPLICATION AND TRANSFER OF QUALIFICATION TECHNIQUES TO THE HUMAN MOBILITY PASTORAL IN CORUMBÁ, MS: BORDER DEMANDS AND INTERNATIONAL MIGRATION. XX p. Master's Dissertation (Stricto Sensu Postgraduate Course at the Master's level in Border Studies, Federal University of Mato Grosso do Sul, Campus do Pantanal, Corumbá, MS). This Dissertation has a general aim: to analyze and implement permanent training practices offered by the Pastoral da Mobilidade Humana and the Circuito de Apoio ao Imigrante to agents who deal daily with the international migration flows at the border involving Brazil-Bolivia in Corumbá, MS. Therefore, it was necessary to carry out investigations about the Scalabrinian Mission, its consequences in Brazil and its vicissitudes at the border. With the expectation of expanding and retraining the PMH volunteer staff, projects were developed with the Circuito Imigrante. The outcome achieved was the updating of concepts and aptitudes of the members involved. The effectiveness of the proposal was hampered by the effects of Covid-19 Pandemic. Keywords: International migration. Border. Corumba. Human Mobility Pastoral.